Tenofovir disoproxil fumarate appears to disrupt the relationship of vitamin D and parathyroid hormone. Issue 7 (October 2018) - ,; Havens, Peter L; Long, Dustin; Schuster, Gertrud U; Gordon, Catherine M; Price, Georgine; Wilson, Craig M; Kapogiannis, Bill G; Mulligan, Kathleen; Stephensen, Charles B
Background: Tenofovir disoproxil fumarate (TDF) increases serum parathyroid hormone (PTH) and 1, 25 dihydroxy vitamin D (1, 25-(OH)2 D), and decreases bone mineral density (BMD). Optimal treatment of TDF-associated BMD loss requires an understanding of the primary cause of these abnormalities. Methods: Secondary review of data from two studies of TDF use in youth, comparing the relationship of PTH, 25-hydroxy vitamin D (25-OHD) and 1, 25-(OH)2 D in three groups with varying exposures to TDF: youth without HIV enrolled in a trial of TDF/emtricitabine (FTC) for HIV pre-exposure prophylaxis (PrEP) at baseline (no TDF exposure) and after 12 weeks of TDF (short-term TDF exposure); and youth with HIV treated with TDF-containing combination antiretroviral therapy (cART) for at least 6 months at study entry (long-term TDF exposure). Relationships were evaluated by correlation analyses. Results: Participants ranged in age from 17 to 24 years and >50% were Black/African American. In persons not treated with TDF, PTH had the physiologically appropriate negative correlation with 25-OHD (r=-0.3504, P =0.004). Correlations between PTH and 25-OHD in groups treated with TDF were weaker or absent. With longer term TDF treatment in persons with HIV, 25-OHD and 1, 25-(OH)2 D had the positive correlation similar to that found in vitamin D deficiency. Conclusions: TDF changes the relationship of 25-OHD to PTH, suggesting that in persons using TDF for PrEP or cART, a higher than usual target for serum 25-OHD concentration might be needed to reduce PTH and optimize bone health. Clinical trials registration: NCT01751646 (ATN 109) and NCT01769469 (ATN 117).